Peningkatan Keterampilan Kolaborasi dan Hasil Belajar Matematika Peserta Didik Kelas VII SMP Negeri 4 Madiun Melalui Penerapan Model Problem Based Learning - Putri, Ria Anggelia; Murtafiah, Wasilatul; Hartanto, Henry Yuli (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research was based on the collaboration skills and learning outcomes of students in class VII D SMP Negeri 4 Madiun which were not optimal. The purposes of this study were to increase collaboration skills and math learning outcomes through the PBL model. There were 32 students of class VII D SMP Negeri 4 Madiun as the research subjects. This class action research used Lesson Study design and quantitative descriptive analysis method with observation, questionnaire and test techniques. This research was separated into two sections, namely pre-cycle and cycle (cycle I and cycle II). The results showed that the average collaboration ability increased in the pre-cycle 57.34%, cycle I 70.47%, and in cycle II 80.23%. While the average learning outcomes of students also showed an increase in the pre-cycle (75.05), cycle I (81.29), and cycle II (86.21) with the applied KKTP of 75. As well as the percentage of learning completeness improved in the pre-cycle 71.88%, cycle I 81.25% and cycle II 87.50%.